The Impact of Mediterranean Dietary Intervention on Metabolic and Hormonal Parameters According to BRCA1/2 Variant Type - Oliverio, Andreina; Radice, Paolo; Colombo, Mara; Paradiso, Angelo; Tommasi, Stefania; Daniele, Antonella; Terribile, Daniela Andreina; Magno, Stefano; Guarino, Donatella; Manoukian, Siranoush; Peissel, Bernard; Bruno, Eleonora; et al. (Frontiers in Genetics, 2022)
Female carriers of BRCA1/2 pathogenic variants (mutations) face a high lifetime risk of developing breast and/or ovarian cancer. However, the risk may differs depending on various genetic and non-genetic elements, including metabolic and hormonal factors. We previously showed that a six-month Mediterranean dietary intervention trial reduced body weight, and the levels of insulin-like growth factor I (IGF-I) and other metabolic factors in BRCA mutations carriers. We also found that higher baseline levels of glucose and insulin were significantly associated with BRCA loss of function (LOF) variants. In this study, we evaluated whether BRCA mutation type influence in a different way the metabolic and hormonal response to the dietary intervention in 366 female carriers. LOF variant carriers randomized in the intervention group (IG) showed significantly higher changes in most considered parameters compared to control group (CG). Nonsynonymous variant carriers in the IG showed similar changes, but none of them were statistically significant. Performing the “delta” analysis of differences (intention to treat analysis), we observed that in LOF variant carriers the reduction of insulin levels was significantly more pronounced that in nonsynonymous variant carriers. These findings suggest that the changes in insulin levels might be modulated by a different response to the dietary intervention mediated by BRCA LOF variants.